Pilot Phase II Trial of Imatinib Mesylate in Neurofibromatosis Type 1 patients with Plexiform Neurofibromas - Robertson, Kent A. (Lancet Oncol, 2012)
BACKGROUND: Plexiform neurofibromas (PN) are slow growing chemoradiotherapy resistant tumours arising in patients with neurofibromatosis type I (NF1). Currently there are no viable therapeutic options for patients whose life-threatening plexiform neurofibromas cannot be surgically removed due to proximity to vital body structures. Based on identification of molecular targets in genetic mouse models of human NF1 tumours, we hypothesized that the oral kinase inhibitor, imatinib mesylate, may be effective in targeted treatment of these chemoradiotherapy-refractory tumours. METHODS: An open-label pilot Phase II clinical trial was designed to test whether treatment with imatinib mesylate can decrease volume burden of clinically significant plexiform neurofibromas in NF1 patients. The entry criteria require patients only to have NF1 and a clinically significant plexiform neurofibroma with the specified age limitations (age 3–65). Patients were treated with daily oral imatinib at 440 mg/m(2)/day for children and 800 mg/day for adults divided twice daily for 6 months. The primary endpoint measure of significant response was a 20% or more reduction in plexiform size by sequential volumetric MRI imaging. Clinical data was analyzed on an intent to treat basis, however to determine the activity of imatinib on NF1-related plexiform tumours, patients able to take imatinib for 6 months were evaluated for their response. Secondary outcomes included evaluation of safety of imatinib mesylate in this group of patients. The trial is registered at http://clinicaltrials.gov/; study number 0512-25. The trial currently is closed to enrollment, however there is a single patient that continues to respond and remains on study. FINDINGS: On an intent to treat basis, 6 out of 36 patients or 17% (95% CI: 6 – 33%) experienced objective response to imatinib mesylate. In the evaluable study population of patients (n=23) who received drug for at least six months, six patients (26%; 95% CI: 10 – 48%) experienced ≥ 20% decrease in volume of one or more plexiform tumours and 30% of study patients had symptomatic improvement. We noted significant inter-patient and intra-patient heterogeneity of plexiform neurofibroma response. Toxicity of drug was comparable to previous reports in patients with chronic myelogenous leukemia. The most common adverse events were reversible skin rash (5 patients) and edema with weight gain (6 patients). More serious adverse events included reversible grade 3 neutropenia (2 patients) and grade 4 transaminitis (one patient). INTERPRETATION: Imatinib mesylate caused disease regression in 26% of evaluable patients with clinically significant plexiform neurofibromas due to neurofibromatosis type 1. These results warrant confirmation in a larger multi-institutional clinical trial aimed at this patient population. These findings provide the first demonstration of radiographic volumetric tumour reduction in response to medical therapy in patients with NF1 plexiform neurofibromas using imatinib mesylate based on studies in a pre-clinical genetic mouse model. These translational studies form the framework whereby other agents may be tested/compared to imatinib in the pre-clinical model and moved into the clinic advancing development of more effective therapies for NF1-related plexiform neurofibromas.